1999
DOI: 10.1002/etc.5620180705
|View full text |Cite
|
Sign up to set email alerts
|

Fish mercury distribution in Massachusetts, USA lakes

Abstract: The sediment, water, and three species of fish from 24 of Massachusetts' (relatively) least‐impacted water bodies were sampled to determine the patterns of variation in edible tissue mercury concentrations and the relationships of these patterns to characteristics of the water, sediment, and water bodies (lake, wetland, and watershed areas). Sampling was apportioned among three different ecological subregions and among lakes of differing trophic status. We sought to partition the variance to discover if these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 21 publications
2
27
0
Order By: Relevance
“…Mercury concentrations were generally lower in bottom dwellers than in predators. This is consistent with the findings of Rose et al (1999) and Peterson et al (2007) where piscivorous predator species typically accumulated higher concentrations of mercury than non-piscivores. Statistical analysis showed that mercury concentrations in predators occurred above the EPA 300 ppb mercury fish tissue criterion at nearly half of the lakes in the sampled population.…”
Section: Discussionsupporting
confidence: 91%
“…Mercury concentrations were generally lower in bottom dwellers than in predators. This is consistent with the findings of Rose et al (1999) and Peterson et al (2007) where piscivorous predator species typically accumulated higher concentrations of mercury than non-piscivores. Statistical analysis showed that mercury concentrations in predators occurred above the EPA 300 ppb mercury fish tissue criterion at nearly half of the lakes in the sampled population.…”
Section: Discussionsupporting
confidence: 91%
“…For example, fish and other aquatic animals take up methylmercury by direct absorption from the water, through the gill membrane and skin, as well as by the ingestion and successive digestion of contaminated food. The brown bullhead (Ameiurus nebulosus) uptakes mercury from its food but also an important percentage from the water, because of its scaleless permeable skin (Rose et al 1999). Jernelof (1972) estimated that the pike (Exos lucius) derived 50% of its methylmercury body burden from food and 50% from water, whereas whitefish (Coregonus clupeiformis) derived only 10% from food and 90% from water.…”
Section: Uptake and Loss Of Pollutantsmentioning
confidence: 99%
“…From the results of a study on mercury concentration in the muscle of three fish species (Perca flavescens, Micropterus salmoides, Ameiurus nebulosus) from 24 lakes of Massachusetts, Rose et al (1999) attributed the differences between the species to their growth and metabolic rates, without excluding other causes. They found a good positive correlation between the weight of Micropterus and the mercury concentration in its body.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have revealed important relationships between Hg bioaccumulation, lake characteristics, local deposition patterns, and watershed attributes Watras et al, 1998;Rose et al, 1999;Kamman et al, 2005). Earlier studies focused on physico-chemical variables and fish in largely forested lake systems (Hakanson et al, 1988;Suns and Hitchin, 1990;Simonin et al, 1994).…”
Section: Introductionmentioning
confidence: 99%